Agenda Setting in the formation of Salamrejo Village Regulation Number 7 of 2016 concerning the Anniversary of Salamrejo Village, Kapanewon Sentolo, Kulon Progo Regency - Galuh Kusuma Ningtantri; John Chrysostomus Sado; Tanti Sadmawati; Kirana Rilla Pratama; Adji Suradji Muhamad (International Journal of Social Welfare and Family Law, 2024)
The aim of this research is to provide an overview of the implementation of agenda setting in the formation of Salamrejo Village Regulation Number 7 of 2016 concerning the Anniversary of Salamrejo Village, Kapanewon Sentolo , Kulon Progo Regency. The research method used a qualitative descriptive method, namely an effort to collect, compile and interpret existing data and then analyze the data. The research concluded that the agenda setting process began with a more " jagongan " discussion between the Village Head, community leaders, Village Consultative Body, Salamrejo District Community Empowerment Institution, Family Welfare Empowerment and Karang Taruna , followed by meetings, team formation and subsequent literature studies. make a decree called the Salamrejo District Anniversary Village Regulation which is used as a guideline in carrying out activities so that the Government Work Plan (RKP) in the use of the Regional Revenue and Expenditure Budget (APBDES) can be accounted for.